2020
DOI: 10.1080/09168451.2019.1664891
|View full text |Cite
|
Sign up to set email alerts
|

TNNT1, a prognostic indicator in colon adenocarcinoma, regulates cell behaviors and mediates EMT process

Abstract: Slow skeletal muscle troponin T (TNNT1) has been reported to be correlated with several cancers, but there are no evidences proving that TNNT1 is required in colon adenocarcinoma (COAD). TNNT1 expression in COAD tissues and its prognostic significance were acquired from TCGA database. The proliferative, migratory, and invasive abilities of COAD cells were detected by CCK-8 and transwell assays, respectively. Correlations between TNNT1 and epithelial–mesenchymal transition (EMT)-related markers were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
4
11
0
1
Order By: Relevance
“…Among the 144 DEGs between BRAF mutation and BRAF wild-type subtypes, BST2, CALB2, TNNT1, ENO2, HOXC6, and SYNGR3 were associated with overall survival in the TCGA dataset. Similar results were found that elevated BST2 level, HOXC6, and TNNT1 level are correlated with poor prognosis in colon cancer patients, while TNNT1 protein may be mediated through the process of epithelial–mesenchymal transition ( Chiang et al, 2015 ; Hao et al, 2020 ; Yuan et al, 2020 ). CALB2 is a calcium binding protein from the EF hand family and is expressed in the majority of poorly differentiated colon cancer ( Häner et al, 2010 ).…”
Section: Discussionsupporting
confidence: 81%
“…Among the 144 DEGs between BRAF mutation and BRAF wild-type subtypes, BST2, CALB2, TNNT1, ENO2, HOXC6, and SYNGR3 were associated with overall survival in the TCGA dataset. Similar results were found that elevated BST2 level, HOXC6, and TNNT1 level are correlated with poor prognosis in colon cancer patients, while TNNT1 protein may be mediated through the process of epithelial–mesenchymal transition ( Chiang et al, 2015 ; Hao et al, 2020 ; Yuan et al, 2020 ). CALB2 is a calcium binding protein from the EF hand family and is expressed in the majority of poorly differentiated colon cancer ( Häner et al, 2010 ).…”
Section: Discussionsupporting
confidence: 81%
“…To obtain a deeper understanding of the characteristics of miR‐873 expression in CRC, the expression levels of miR‐873 in normal tissues and CRC tissues and CRC cell lines were detected by RT‐PCR, respectively. The results obtained indicated that, compared to normal tissues, the expression levels of miR‐873 in CRC tissues and CRC cell lines were evidently down‐regulated, which was consistent with a previous study (Figure B and C) . To confirm the target relationship between TNNT1 and miR‐873, HT29 and SW480 cell lines were selected to build a model of miR‐873 overexpression and a model of miR‐873 inhibition (Figure D).…”
Section: Resultssupporting
confidence: 87%
“…GenePharma (Shanghai, China) synthesized and provided pcDNA3.1/TNNT1 and pcDNA3.1 plasmid. Ribobio Co., Ltd (Guangzhou, China) supplied siRNA targeting TNNT1, control siRNA, miR‐873 mimics, negative control mimics, miR‐873 inhibitor and control inhibitor, and the sequences were designed as described previously . Plasmids were transfected with Lipofectamine 2000 reagent in accordance with the manufacturer's instructions (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, reports have suggested that TNNT1 could contribute to cell proliferation in breast cancer [53]. Moreover, Hao et al [54] reported that TNNT1 might promote the progression of colon adenocarcinoma by mediating the epithelial-mesenchymal transition process. In the present study, we found that TNNT1 was involved in cardiac muscle contraction, regulation of skeletal muscle contraction, troponin 1, and C binding molecular functions and associated with poor prognosis of LUAD.…”
Section: Discussionmentioning
confidence: 99%